2013
DOI: 10.1111/jocn.12111
|View full text |Cite
|
Sign up to set email alerts
|

‘Safe enough in here?’: patients' expectations and experiences of feeling safe in an acute psychiatric inpatient ward

Abstract: Nurses need to be sensitive to the possibility that patients feel unsafe in the absence of obvious threat. Institutional structures that challenge patients' sense of safety must be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 50 publications
6
62
1
2
Order By: Relevance
“…Stenhouse (2013) uses the term "sanctuary harm" to capture the potentially damaging impact of abuse or violence that occurs to patients who have been admitted to a mental health unit. Jones et al (2010) see wards as both safe and unsafe places.…”
Section: Introductionmentioning
confidence: 99%
“…Stenhouse (2013) uses the term "sanctuary harm" to capture the potentially damaging impact of abuse or violence that occurs to patients who have been admitted to a mental health unit. Jones et al (2010) see wards as both safe and unsafe places.…”
Section: Introductionmentioning
confidence: 99%
“…In 11 studies, it was identified that lack of information and communication contributed to patients feeling unsafe (Stenhouse 2013, Wassenaar et al 2014 (Vaismoradi et al 2011). A general perception of a lack of quality assessment, planning or implementation of care is presumed by patients to contribute to their feelings of being unsafe.…”
Section: Information and Communicationmentioning
confidence: 99%
“…Jones et al (2010), Stenhouse (2013), Lasiter (2011), Lovink et al (2015, Mollon (2014) and Rathert et al (2011), all identified that lack of staff availability, including visibility, presence-physically and psychologically, and perceptions of being 'short staffed', all added to patients feeling less safe (Rathert et al 2011). Lack of physical presence was perceived as being significant (Mollon 2014, Lasiter 2011, as was the lack of engagement with patients described as a lack of psychological or physical presence (Mollon 2014).…”
Section: Loss Of Controlmentioning
confidence: 99%
See 2 more Smart Citations